PERSEPSI GURU MI KABUPATEN BIREUEN TERHADAP PENGGUNAAN APLIKASI GURU KELAS (AGK) DALAM PENGISIAN RAPOR BERBASIS K-13 (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2019)
This study aims to learn the perception of secondary school teachers in Bireuen, Aceh toward the use of classroom teacher administration (AGK) software in filling out the K-13 based student report  cards based. The application helps the classroom teachers fill out student grades effortlessly. This descriptive quantitative study used surveys, in collecting the data, distributed to 60 teachers at 5 secondary schools in Bireuen. The data were then analyzed using descriptive statistics (frequency, average and percentage) to determine teacher perception stages toward the AGK software. The results show that the secondary school teachers in Bireuen had a high perception toward the software. It eased the teachers in filling out the student grades. Therefore, it that secondary school teachers who still out the cards manually are suggested to utilize the software when filling out the student report cards.
Keywords: Perception; Software; Classroom Teacher Administration; Student Report Cards; 2013 Curriculum